2021
DOI: 10.3390/vaccines9040343
|View full text |Cite
|
Sign up to set email alerts
|

Development of Diagnostic Tests Provides Technical Support for the Control of African Swine Fever

Abstract: African swine fever is a highly contagious global disease caused by the African swine fever virus. Since African swine fever (ASF) was introduced to Georgia in 2007, it has spread to many Eurasian countries at an extremely fast speed. It has recently spread to China and other major pig-producing countries in southeast Asia, threatening global pork production and food security. As there is no available vaccine at present, prevention and control must be carried out based on early detection and strict biosecurity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 137 publications
0
16
0
Order By: Relevance
“…At present, based on CRISPR/Cas12a-based nucleic acid detection technology, recombinase polymerase amplification and gold nanoparticles technology have been reported for the rapid detection of ASFV. However, its commercial use still needs a particular time [ 33 36 ]. Currently widely used detection technology is the real-time PCR targeting the p72 gene, which shows high sensitivity and specificity.…”
Section: Strategies For Generating Asf Lav Candidatesmentioning
confidence: 99%
“…At present, based on CRISPR/Cas12a-based nucleic acid detection technology, recombinase polymerase amplification and gold nanoparticles technology have been reported for the rapid detection of ASFV. However, its commercial use still needs a particular time [ 33 36 ]. Currently widely used detection technology is the real-time PCR targeting the p72 gene, which shows high sensitivity and specificity.…”
Section: Strategies For Generating Asf Lav Candidatesmentioning
confidence: 99%
“…Moreover, it requires a large and well-established database to support the results, which have limited development in the field of rapid detection of viruses (Pelletier et al 2011). In addition, enzyme-linked immunosorbent assay (ELISA) is the most typical immunological method, which has been approved for a lot of diseases detection by FDA and OIE (Kazakova et al 2017;Qiu et al 2021;Zhang et al 2020). But many researchers had found that ELISA showed low sensitivity of 77.2% in the commercial kits, poor thermal stability, poor repeatability, and false positive due to the interference of autoantibodies (Gallardo et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Strict biosecurity protocols and classic sanitary methods both at the farm and at national levels have been adopted to fight the spread of this virus; however, these strategies are remain insufficient, and in some countries they are difficult or impossible to follow owing to the lack of available resources [ 9 , 10 , 11 , 12 ]. As there are no licensed vaccines or treatments available, the most important control strategies for ASFV are early virus detection, followed by laboratory diagnosis [ 13 ], and the subsequent culling of ASFV-infected animals from the herds to prevent the spread of the virus [ 14 ].…”
Section: Introductionmentioning
confidence: 99%